2015
DOI: 10.1016/j.cognition.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Manual action, fitting, and spatial planning: Relating objects by young children

Abstract: This study uses motion tracking technology to provide a new way of addressing the development of the ability to prospectively orient objects with respect to one another. A group of toddlers between 16-33 months of age (N=30) were studied in an object fitting task while they wore reflective markers on their hands to track spatial adjustments in three dimensions. Manual displacements of the handheld object were separated into translations and rotations. Results revealed that younger children largely used a two-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 23 publications
(58 reference statements)
3
33
0
Order By: Relevance
“…In our study, both two and three year-old children succeeded on a greater percentage of 3D trials than 2D trials, and this was most evident for two year-olds (see Table 2 ). Jung et al [ 36 ] took a complementary perspective, studying the process by which young children (16–33 months old) integrate rotation and translation of an object while completing a fitting task. These authors show that children between two and three years-old, compared to children16–20 months, better integrate translational and rotational components of movement while bringing a rod to a matching cut-out placed on a table in front of them.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, both two and three year-old children succeeded on a greater percentage of 3D trials than 2D trials, and this was most evident for two year-olds (see Table 2 ). Jung et al [ 36 ] took a complementary perspective, studying the process by which young children (16–33 months old) integrate rotation and translation of an object while completing a fitting task. These authors show that children between two and three years-old, compared to children16–20 months, better integrate translational and rotational components of movement while bringing a rod to a matching cut-out placed on a table in front of them.…”
Section: Discussionmentioning
confidence: 99%
“…Translations refer to the movement of an object to a new location and rotations refer to a change in the orientation of the object (Landau & Spelke, 1988). During the preschool years, young children begin to integrate translations and rotations when they stack objects (Hayashi & Takeshita, 2009; Verdine et al, 2014) or fit objects into apertures (Jung, Kahrs, & Lockman, 2015; Örnkloo & von Hofsten, 2007; Shutts, Örnkloo, von Hofsten, Keen, & Spelke, 2009; Street, James, Jones, & Smith, 2011), transporting the object to its target (translation) while they orient it (rotation) with respect to that target.…”
Section: Spatial Demands and Handled Objectsmentioning
confidence: 99%
“…Children's performance on object alignment or fitting tasks has been studied previously in young children, but mainly with non-handled objects (Jung et al, 2015; Örnkloo & von Hofsten, 2007; Shutts et al, 2009; Street et al, 2011, but see Barrett, Davis, & Needham, 2007). Results from several studies indicate that prior to the end of the second year, children evidence difficulty in coordinating translations and rotations when fitting objects without handles into apertures.…”
Section: The Current Studymentioning
confidence: 99%
“…Kinematic studies in young children have additionally reported a developmental progress in coordinating translations and rotations of handled objects to be fitted into apertures. The results suggest an improved spatial planning ability over the toddler years (Jung, Kahrs, & Lockman, , ).…”
Section: Introductionmentioning
confidence: 96%